Visit-to-visit variability and seasonal variation in blood pressure: Combination of Antihypertensive Therapy in the Elderly, Multicenter Investigation (CAMUI) Trial subanalysis*. (August 2015) - Sato, Nobuyuki; Saijo, Yasuaki; Sasagawa, Yutaka; Morimoto, Hideo; Takeuchi, Toshiharu; Sano, Hiroaki; Koyama, Satoshi; Takehara, Naofumi; Morita, Kazutoyo; Sumitomo, Kazuhiro; Maruyama, Junichi; Kikuchi, Kenjiro; et al.
Abstract Background: Combination antihypertensive therapy with an angiotensin receptor blocker (ARB) and a calcium channel blocker (CCB) or diuretics is common. This subanalysis investigated blood pressure (BP) variability in patients receiving ARB-based combination therapy. Methods: In a prospective, randomized, open-label trial, hypertensive outpatients (≥65 years) who did not achieve their target BP with ARB monotherapy switched to losartan 50 mg/hydrochlorothiazide 12.5 mg (ARB + D) or ARB plus amlodipine 5 mg (ARB + C) for 12 months. Clinic BP and heart rate (HR), measured every 3 months, visit-to-visit variability and seasonal variation were evaluated. Results: No significant between-group differences in average, maximum, or minimum systolic or diastolic BP, or HR, were found. Visit-to-visit BP variability (systolic) was significantly higher in the ARB + D group than in the ARB + C group. When each group was subdivided into two seasonal groups (summer and winter), no significant between-group differences in BP were found. Multivariate regression analyses showed a tendency toward negative correlation between outdoor temperature and urinary albumin:creatinine ratio and estimated glomerular filtration rate at 12 months in the ARB + D group. Conclusion: Combination therapy with an ARB plus a CCB may be preferable to that with an ARB plus diuretics for decreasing BP variability. As for seasonal variability, both treatments can be used safely regardless of season.